Pengaruh Model Guided Discovery Learning dengan Pendekatan Pendidikan Matematika Realistik Indonesia terhadap Kemampuan Berpikir Kreatif Siswa SMPN 12 Bekasi - Sari Lingga Buana, Yunan (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2024)
The purpose of this study was to determine the effect of guided discovery learning model with Indonesian realistic mathematics education approach on students' creative thinking ability. This research method is a quasi-experiment method with posttest only control group design. The sampling technique used cluster random sampling so that the samples obtained were VII.A and VII.C classes. The data collection technique used a description test of students' creative thinking skills. Data analysis was carried out twice, namely before and after the research was conducted. Based on the results of hypothesis testing using t-test with a significance level of α = 0.05 it shows that the average creative thinking ability of students in the experimental class is higher than the average creative thinking ability of students in the control class. The value of the influence with Cohen's effect size shows a percentage of 66%. Based on the results of the study, it can be concluded that there is an effect of the application of the guided discovery learning model with an Indonesian realistic mathematics education approach on the creative thinking skills of students at SMP Negeri 12 Bekasi. Translated with DeepL.com (free version)